Maximum Control Water Level (CWL) Jatibarang Dam to Avoid The Possibility of Overtopping Due to Flood 100 Years - Sutopo, Yeri; Utomo, Karuniadi Satrijo (Semarang State University, 2019)
The study of the maximum water level control of the Jatibarang reservoir is to avoid the possibility of overtopping due to flooding after 100 years return period, therefore it is necessary to take into account the changes in land use, which were once shrubs turned into settlements. Changes in land use result in an increase in the drainage coefficient which results in an increase in surface runoff so that the flood discharge in the river becomes even greater. Jatibarang Dam in Semarang at the time of planning was still designed to use flood discharge return period of Q 50 years; whereas the water structure has included a hazard level classification, so flood safety standards should have been used return period of the Q 100 years. The aims of this study are (1) to analyze the maximum CWL value in the main spillway of the Jatibarang dam based on the analysis of flooding due to Q 100 years; and (2) comparing the maximum CWL value of the main overflow dam Jatibarang results of planning using Q 50 years with the maximum CWL value of the main overflow dam due to flood discharge Q 100 years.This type of research was a survey. Data collection methods used were observation and documentation. The observation method was used to determine the coordinates of the dam spillway, which was then used to make a Jatibarang dam spillway watershed map and directly observe the Jatibarang dam spillway construction. The documentation method was used to collect rainfall data.The inflow flood hydrograph for a 100 year return period is 1838.84 m3/s, while the outflow is 227.57 m3/s, thus the Jatibarang reservoir can accommodate or store flood discharge of 1611.27 m3/s. The maximum elevation of the Jatibarang dam spillway is +155.3. The flood routing results show that the highest elevation is +154.05 at ten time. Comparison between the highest elevation of Q 100 years flood routing results which is equal to +154.05 is lower when compared to the maximum elevation of the Jatibarang dam spillway which is equal to +155.3; so that the main spillway elevation is still able to overcome of Q 100 years. Thus the Jatibarang dam spillway is still safe against the highest elevation of flood Q 100 years.